REDUCING PUBLIC SKEPTISM THROUGH CORPORATE SOCIAL RESPONSIBILITY COMMUNICATION - Uljanatunnisa, Uljanatunnisa; Febriany; Hidayah, Della Bagusnur (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Pembangunan Nasional Veteran Jakarta, 2023)
This study aims to analyze Corporate Social Responsibility communication as an effort to reduce public skepticism towards PT HM Sampoerna, this is based on the pros and cons of the CSR program and CSR communication especially in controversial industries such as cigarette companies. Using four dimensions of CSR initiative messages, namely CSR Commitment, CSR impact, CSR Motive and CSR FIT with a qualitative content analysis method, the primary data of this study are posts on the official social media account @insidesampoerna during the data collection period from 1 January 2023 to 30 May 2023 Based on the results of the coding, the researcher found that most of the company's CSR communications used the message of the CSR Impact initiative which was represented by the description